Enhanced biocrude production from hydrothermal conversion of municipal sewage sludge via co-liquefaction with various model feedstocks. Issue 31 (13th July 2022) - Wang, Wenjia; Du, Hongbiao; Huang, Yuanyuan; Wang, Shaobo; Liu, Chang; Li, Jie; Zhang, Jinglai; Lu, Shuai; Wang, Huansheng; Meng, Han
Abstract : Hydrothermal co-liquefaction has the potential to improve biocrude yield. Abstract : Hydrothermal co-liquefaction has the potential to improve biocrude yield. To investigate the influence of various types of biomass on co-liquefaction with municipal sewage sludge (MSS), experiments on MSS with three kinds of model feedstocks (soy oil, soy protein, and starch) were carried out. Reaction temperatures of 300, 320, and 340 °C proved to be the appropriate reaction temperatures for the highest biocrude yield for soy oil, soy protein, and starch, respectively. A synergistic effect on the biocrude yield of co-liquefaction was proved, and starch showed the highest synergistic effect with a 57.25% increase in biocrude yield, while soy oil only presented a slight synergistic effect. Thermal gravimetric analysis (TGA) results suggested that co-liquefaction with soy oil increased the light oil fractions in biocrude by 20.81%, but protein and starch led to more heavy oil fractions. Gas chromatography-mass spectrometry (GC-MS) indicated that co-liquefaction with protein or starch produced more cyclic compounds in the biocrude, while almost no new components appeared from co-liquefaction with soy oil.